2020
DOI: 10.3390/cells9030745
|View full text |Cite
|
Sign up to set email alerts
|

Spermatogonial Stem Cells for In Vitro Spermatogenesis and In Vivo Restoration of Fertility

Abstract: Spermatogonial stem cells (SSCs) are the only adult stem cells capable of passing genes onto the next generation. SSCs also have the potential to provide important knowledge about stem cells in general and to offer critical in vitro and in vivo applications in assisted reproductive technologies. After century-long research, proof-of-principle culture systems have been introduced to support the in vitro differentiation of SSCs from rodent models into haploid male germ cells. Despite recent progress in organotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 156 publications
0
42
0
1
Order By: Relevance
“…SSCs are the only adult stem cells that pass genes to offspring and have been used in the treatment of male reproductive system diseases and animal genome editing [ 5 ]. This study investigated for the first time the effect of melatonin on goat SSCs during cryopreservation and explored its protective mechanisms in terms of oxidation, apoptosis, and autophagy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SSCs are the only adult stem cells that pass genes to offspring and have been used in the treatment of male reproductive system diseases and animal genome editing [ 5 ]. This study investigated for the first time the effect of melatonin on goat SSCs during cryopreservation and explored its protective mechanisms in terms of oxidation, apoptosis, and autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…SSCs both self-renew to keep the stability of the stem cell pool and differentiate to contribute to spermatogenesis, thereby maintaining the homeostasis of testicular cells [ 3 ]. As adult stem cells that produce spermatocytes, SSCs transmit genetic information to the next generation [ 4 , 5 ]. Studies have shown that SSCs can be cultured and passaged in vitro, and differentiate into sperm after transplantation [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The purification of SSCs will be specifically discussed later on. Importantly, for detailed lists on some of the most commonly used markers for the effective FACS sorting of SSCs from the testes of different mammals, recent review articles specifically addressing this topic, and tables therein, can be consulted [ 116 , 117 ]). Together, single-cell analyses have identified new subsets of spermatogonia and unveiled the dynamic nature of spermatogenic initiation.…”
Section: Fcm As a Preparative Tool In Spermatogenic Studiesmentioning
confidence: 99%
“…Ibtisham et al summarize the progress made in offering efficient methods for SSC isolation, characterization, in vitro 2D and 3D suspension culture systems, and in vitro differentiation, particularly using primate models. The authors also review some of the salient proposed approaches for the preservation and restoration of fertility in prepubertal and pubertal patients using currently-available and potential future SSC-driven biotechnological strategies [ 36 ].…”
Section: Stem Cell-based Therapymentioning
confidence: 99%
“…This Special Issue includes both research [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] and reviews articles [ 10 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ] which cover wide ranges of stem cell research: adult stem cells, cancer stem cells, pluripotent stem cells, and complex 3D organoid/cell aggregate models [ 26 , 27 , 33 ], with the focuses on stem cell biology/technology [ 10 , 23 , 24 , 25 , 26 , 31 , 32 , 34 ], and stem cell-based disease modeling [ 10 , 27 , 29 , 31 , 33 , 38 , 43 ] and cell therapy [ 24 , 28 , 30 , 32 , 35 , 36 , 37 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%